Modes of Philology in Medieval South India - Cox, Whitney (Philological Encounters Monographs, 2016)
In Modes of Philology in Medieval South India, Whitney Cox rethinks the textual practices of a diverse collection of scholars and poets writing in Sanskrit, Tamil, and Prakrit in far southern India between the 11th and the 14th centuries CE. Readership: Scholars and post-graduate students in any of the following fields: medieval Indian history; Sanskrit and Tamil studies; the history Indian religions, especially the Tantric traditions; historians of philology.